Visual Brief Cards for Advertising Design: A Structured UI/UX Framework for Turning Creative Intentions into Graphic Design Decisions (International Journal of Graphic Design, 2025)
Automatic graphic design systems increasingly transform short creative intentions into visual assets, yet designers still need intermediate decisions that are easy to inspect, compare, and revise. This paper proposes Visual Brief Cards, a structured UI/UX framework that converts a design intention into a compact card containing headline, sub-heading, visual object, background mood, keywords, call to action, brand tone, design risk, and typography guidance. In response to the need for a stronger empirical basis, the revised evaluation uses OpenCOLE as the primary benchmark. All OpenCOLE splits were loaded, and the main quantitative comparison is reported on the held-out test split of 2,375 rows; GraphicBench test data and DEsignBench-Prompts are used as secondary checks. Three brief formats are compared under the same deterministic implementation: a free-form brief, a conventional JSON brief, and the proposed Visual Brief Card. On OpenCOLE test data, the card achieved the highest field reconstruction F1 (0.259), complete field coverage (1.000), measurable design-risk recovery (0.302), and the lowest computational scan-time proxy (1.061 s). Free-form text retained the highest TF-IDF semantic similarity (0.252) because it preserved the source wording with less compression. These results support a narrower claim: labeled card structure improves the visibility and recoverability of intermediate design decisions, while human-subject work is still required before making claims about designer trust, workload, or usability in practice.